Role of Positive-Negative Symptoms of Schizophrenia on Motivation and Cognitive Problems - Iram Naz; Laiba Ahmed (Indus Journal of Social Sciences, 2025)
Investigating positive-negative symptoms, motivation, and cognitive functioning in individuals with schizophrenia was the aim of the current study. In this cross-sectional study, 70 outpatients with schizophrenia who were 19 years of age or older participated. Every participant finished the Montreal Cognitive Assessment Scale (MoCA), the Situational Motivation Scale (SIMS), and the Brief Psychiatric Rating Scale (BPRS-4.0). The hypothesis that positive symptoms would boost motivation and have no effect on cognitive functioning in schizophrenia patients while negative symptoms would lower motivation and cognitive functioning was examined using linear regression. The results reflected that positive symptoms significantly increase the motivation and had no effect on cognitive functioning in schizophrenic patients. The results also have revealed that negative symptoms significantly decrease the motivation patients whereas it was a non-significantly predictor of cognitive functioning in schizophrenic patients. These findings might help in development and providing interventions to schizophrenic dealing with problems with motivation and cognitive functioning.